Epigenetics in endometrial carcinogenesis – part 2: histone modifications, chromatin remodeling and noncoding RNAs. (June 2017) - Bartosch, Carla; Lopes, José Manuel; Jerónimo, Carmen
Carcinogenesis is a multistep multifactorial process that involves the accumulation of genetic and epigenetic alterations. In the past two decades, there has been an exponential growth of knowledge establishing the importance of epigenetic changes in cancer. Our work focused on reviewing the main role of epigenetics in the pathogenesis of endometrial carcinoma, highlighting the reported results concerning each epigenetic mechanistic layer. In a previous review, we assessed DNA methylation alterations. The present review examines the contribution of histone modifications, chromatin remodeling and noncoding RNA alterations for endometrial carcinogenesis.